Pengaruh Pemberian Biosaka dan Pupuk NPK terhadap Pertumbuhan dan Produksi Tanaman Sawi Hijau (Brassica juncea L.) serta Pemanfaatannya sebagai Leaflet - Viona Aura Maharani (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Green mustard (Brassica juncea L.) is a horticultural crop that is widely consumed because it is rich in nutrients and easily available at an affordable price. Conversely, crop yields often declines due to pest attacks and soil nutrient deficiencies. Therefore, the application of biosaka as a plant elicitor combined with NPK fertilizer was expected to increase plant growth and productivity. The purpose of this study was to analyze the effect of biosaka and NPK fertilizer application on the growth and yield of green mustard (Brassica juncea L.), as well as to present the results in an informative printed leaflet. This research was conducted at the Agrotechnopark Greenhouse, University of Jember using a completely randomized factorial design with two treatment factors. The first factor was the concentration of biosaka: B0 (0ml/L), B1 (2.5ml/L), B2 (4.5ml/L), and B3 (6.5ml/L). The second factor was the NPK fertilizer dose: P0 (0g), P1 (3g/polybag), P2 (5g/polybag), and P3 (8g/polybag). The variables observed included plant height, number of leaves, leaf area, fresh weight, production weight, dry weight, growth rate, harvest index, and abiotic factors. Data analysis was performed using ANOVA followed by Duncan's Multiple Range Test (DMRT). The results showed that the application of biosaka and NPK fertilizer had a significant effect on several parameters of green mustard (Brassica juncea L.) plant growth and production. The best results were obtained from the combination of 4.5 ml/L biosaka and 3g/polybag NPK fertilizer, that improved plant growth and yield compared to other treatments. In addition, the leaflets developed from this research were evaluated by three validators and categorized as suitable for use as an effective information medium for farmers and the general public.
FINALISASI oleh Arif 2026 Mei 26
Keywords: Biosaka; Leaflet; Pupuk NPK; Sawi hijau